26 Initial Orthostatic Hypotension in Older Persons: Results from the Malaysian Elders Longitudinal Research Study. (20th December 2019) - Saedon, Nor Izzati; Frith, James; Goh, Choon-Hian; Kamaruzzaman, Shahrul Bahyah; Khor, Hui Min; Kamaruzzaman, Shahrul Bahyah; Tan, Maw Pin; Chin, Ai-Vyrn; Ahmad, Wan Azman Wan; Tan, Kit Mun
Abstract: Objectives: Initial orthostatic hypotension (IOH) is defined as a reduction in systolic or diastolic blood pressure (1) of 40 mmHg or 20 mmHg or greater within 15 seconds of standing. However, little is known about the characteristics of individuals with IOH and its relevance in the older population. The present study aimed to determine factors associated with IOH and classical orthostatic hypotension (COH) and their relationship with physical, functional and cognitive performance. Design: Cross-sectional observational study. Setting and Participants: Individuals aged ≥55 years were recruited through the Malaysian Elders Longitudinal Research (MELoR) study and continuous non-invasive BP was monitored over five minutes of supine rest and three minutes of standing. Measures: Physical performance was measured using timed up and go, functional reach (FR), hand grip (HG) and Lawton's functional ability scale; cognition was measured with Montreal Cognitive Assessment (MoCA). BP response to standing was categorized as non-OH, COH, IOH or COH and IOH Results: 1245 participants were recruited, 623 (50%) had COH, 165 (13%) had IOH and 145 (12%) met the criteria for COH and IOH. COH was associated with increasing age, hypertension, transient ischemic attacks, diabetes mellitus, anti-hypertensive medications and reduced functional reach compared to individuals without COH. IOH was associated with younger age, normo-tension, and the absence of cerebrovascular disease or diabetes. Individuals with IOH had significantly better TUG, FR and HG scores compared to individuals without IOH. Conclusions: This study suggests that IOH is associated with better physical performance. Further research is now required to fully elucidate the clinical relevance of IOH and its relationship to COH, as well as determine appropriate clinical cut-offs.